Pengaruh Pengungkapan Laporan Keberlanjutan dan Tax Avoidance Terhadap Manajemen Laba Perusahaan yang Terdaftar di Jakarta Islamic Index (JII70) Periode 2020-2024 - Roosyiidah, Roosyiidah; Yulianti, Lina; Muslih, Rd. Amar (Akuntansi dan Manajemen, 2025)
The profit presented in financial statements serves as the main indicator used by stakeholders in decision-making. Companies often use earnings management practices to generate profits that attract investor interest. This study aims to find and analyze the influence of sustainability report disclosure and tax avoidance on earnings management in companies listed on the JII70 index in 2020-2024. This study uses secondary data from the companies' financial statements, annual reports, and sustainability reports. The sampling technique was carried out through purposive sampling, resulting in 16 companies being selected as research samples. Panel regression analysis is the test used to study the relationship between sustainability report disclosure and tax avoidance on earnings management. The results of this study show that sustainability reports disclosure, as measured by SRDI, has a significant negative impact on earnings management, and tax avoidance, measured by ETR, has a significant positive impact on earnings management. Furthermore, simultaneous testing shows that sustainability report disclosure and tax avoidance have a significant effect on earnings management.